Direito à intimidade : uma reflexão crítica da submissão obrigatória à identificação do perfil genético para fins criminais - Santos, George Maia (2017)
This present work aims to demonstrate that the mandatory submission convicted of a crime committed, intentionally, with serious violence against person or heinous crime, to identify the genetic profile by DNA extraction - deoxyribonucleic acid, although by proper and painless technique is offensive to fundamental rights. For this purpose, it is part of the overall concept of the right to privacy, which is configured as a negative right or protection against unlawful state mismanagement, in order to protect a need or a basic right to the free individual self-determination. Then genetic intimacy is defined as an asset able to reveal the physical, psychological, behavioral and disease features, which, if disclosed or accessed without the consent of the accused, may generate stigmatization and discrimination of the subject involved, violating in this way, therefore, the right to privacy. In conclusion, we move towards emphasizing besides the right to privacy, compulsory provision of biological material to identify the genetic profile is offensive to fundamental rights to physical liberty or outpatient; physical integrity; to the freedom of religion or conscience; non-discrimination; the silence and non-production of evidences against himself, and in last instance, the biggest vector of all fundamental rights: the dignity of the human person. For the proposed objective, the research will be of an exploratory nature. As for the methodology, it was chosen the deductive method. Finally, as the procedure was adopted bibliographic as type and technique.